The impact of synchronous liver resection on the risk of anastomotic leakage following elective colorectal resection. A propensity score match analysis on behalf of the iCral study group. Issue 11 (November 2021) - Guerra, Francesco; Petrelli, Filippo; Greco, Paola Antonella; Sisti, Valerio; Catarci, Marco; Montalti, Roberto; Patriti, Alberto; ,; Alagna, V.; Amodio, P.; Anania, G.; Angeloni, R.; et al.
Abstract: Introduction: how best to manage patients with colorectal cancer and synchronous liver metastasis is still controversial, with specific concerns of increased risk of postoperative complications following combined resection. We aimed at analyzing the influence of combined liver resection on the risk of anastomotic leak (AL) following colorectal resection. Methods: we reviewed the iCral prospectively maintained database to compare the relative risk of AL of patients undergoing colorectal resection for cancer to that of patients receiving simultaneous liver and colorectal resection for cancer with isolated hepatic metastases. The incidence of AL was the primary outcome of the analysis. Perioperative details and postoperative complications were also appraised. Results: out of a total of 996 patients who underwent colorectal resection for cancer, 206 receiving isolated colorectal resection were compared with a matched group of 53 patients undergoing simultaneous liver and colorectal resection. Combined surgery had greater operative time and resulted in longer postoperative hospitalization compared to colorectal resection alone. The proportion of overall morbidity following combined resection was significantly higher than after isolated colorectal resection (56.6% vs. 37.9%, p = 0.021). Overall, the two groups of patients did not differ neither on the rate of major postoperative complications, nor in terms of AL (9.4% vs. 6.3%, p = 0.381). At specific multivariate analysis, the duration of surgery was the only risk factor independently associated with the likelihood of AL. Conclusions: combining hepatic with colorectal resection for the treatment of synchronous liver metastasis from colorectal cancer does not increase significantly the incidence of AL. Highlights: Over the last decade there has been a growing interest in performing simultaneous resection of colorectal cancer with synchronous metastases confined to the liver. Despite some concerns have been raised regarding a higher risk of postoperative morbidity, clinical evidence focusing on specific surgical-related morbidity is still scarce. This study aims at comparing the relative risk of anastomotic failure in patients receiving isolated colorectal resection vs. patients undergoing colorectal resection in combination with liver metastasis resection. By comparing well-matched groups of patients, this analysis demonstrates that simultaneous colorectal and liver resection does not confer a significantly higher risk of anastomotic leakage as compared to colorectal resection alone.